Impact of GA3 and ZnSO4 on growth and quality flowering of Marigold (Calendula officinalis) (Comprehensive Journal of Science, 2026)
An experiment was carried out at the nursery of the private farm Alaejaylat in Libya during the 2025 season to evaluate the impact of GA3 and ZnSO4 on marigold (Calendula officinalis) development and quality flowering. The experiment utilized a Randomized Complete Block Design (RCBD) with six treatments (control, GA3 100 ml/l + ZnSO4 50 ml/l, GA3 150 ml/l + ZnSO4 75 ml/l, GA3 200 ml/l + ZnSO4 100 ml/l, GA3 250 ml/l + ZnSO4 150 ml/l, and GA3 300 ml/l + ZnSO4 200 ml/l) and three repetitions. Vegetative growth, including plant height, number of leaves, number of branches per plant, total fresh weight, and leaf area index; flowering parameters, including flower diameter, flower fresh weight, number of flowers, flower stalk length, and flowering period; and chemical composition, including nitrogen, phosphate, potassium, total carbohydrates, total chlorophyll, and carotene, were all examined. In comparison to the control treatment, which recorded the lowest mean values of these characteristics, the results showed that high concentrations of GA3 300 ml/l + ZnSO4 200 ml/l recorded the highest values of all growth attributes, including plant height, number of leaves, number of branches/plant, total fresh weight and leaf area index, as well as flower diameter, flower fresh weight, number of flowers, flower stalk length and flowering period, nitrogen, phosphate, potassium, total carbohydrates, total chlorophyll, and carotene. According to the findings of the current study, foliar application of a micronutrient mixture plus GA3 was shown to be the most effective in terms of the vegetative development, blooming, and yield characteristics of Calendula officinalis. This might help you get the most out of growing calendula.
Keywords: Marigold (Calendula officinalis), GA3, Zn, vegetative growth, flowering parameters, chemical composition.